Current indications for antibiotic prophylaxis for the prevention of infective endocarditis in dentistry: A narrative review (Research, Society and Development, 2026)
Infective endocarditis (IE) is a clinically significant infection that primarily affects the endocardium and heart valves and may progress to severe complications with substantial morbidity and mortality. In dentistry, the oral cavity deserves particular attention because it harbors a diverse microbiota and may contribute to transient bacteremia, especially during invasive procedures or in the presence of persistent oral inflammatory conditions. In individuals with predisposing heart abnormalities, such episodes may contribute to the development of cardiac infection. Over time, antibiotic prophylaxis was widely adopted in dental practice; however, more recent recommendations from the American Heart Association (AHA) and the European Society of Cardiology (ESC) have restricted its indication to patients considered at highest risk, such as those with prosthetic heart valves, previous history of IE, and some cases of congenital heart disease. The present study aimed to discuss, through a narrative literature review, the importance of antibiotic prophylaxis in dental procedures and its relationship with the prevention of infective endocarditis. The gathered evidence suggests that antibiotic prophylaxis tends to provide greater benefit in high-risk patients, whereas oral health maintenance, control of infectious foci, and non-pharmacological preventive measures also play a central role in reducing the occurrence of bacteremia.